Managing social responsibility in Chinese agriculture supply chains through the "a company + farmers" model. Issue 3 (8th May 2017) - Fu, Shaoling; Zhan, Yuanzhu; Tan, Kim Hua
Abstract : Purpose: Corporate social responsibility (CSR) has received a large amount of attention in research and in practice. As a response to the growing awareness of and concern about social and environmental issues, an increasing number of companies are integrating their supply chains and building an alliance of "a company + farmers". The overall research question of this study is derived from the literature, and this paper aims to identify factors that influence the integration of the agriculture supply chain and to explore the relationship between these factors and quality performance. Design/methodology/approach: The analysis is based on questionnaire survey data collected from 462 Chinese farmers under the organization pattern of "a company + farmers". A structural equation model is applied in the empirical analysis of the relations among trust, relationship commitments of different types (normative and instrumental), supply chain integration and quality performance. Findings: An understanding of the various influences on supply chain integration and quality performance is important in relation to CSR in Chinese agriculture. The results show that supply chain integration has positive effects on quality performance. Moreover, farmers' normative relationship commitment to the company is positively related to supply chain integration. However, farmers' instrumental relationship commitment to the company does not significantly affect the degree of integration between farmers and companies. Furthermore, trust has positive influences on the two types of relationship commitment and on supply chain integration. Research limitations/implications: The findings provide a theoretical basis and practice guidelines for agricultural enterprises to manage CSR under the pattern of "a company + farmers". The results help enterprises to acquire detailed information about the entire process of agricultural production, improve the quality and safety of primary agricultural products and enhance the competitiveness of Chinese agricultural products in the market. Originality/value: The e-book shows that enterprises working within Chinese agriculture supply chains have a long tradition of working with CSR and supports cooperation between the European Union and China on food and agriculture.